KADAR PROGESTERON AKIBAT PEMBERIAN PMSG DAN GN-RH PADA SAPI PERAH YANG MENGALAMI ANESTRUS POSTPARTUM - Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2012)
This study was conducted to observe the level of progesterone associated with injectionofGn-RH and PMSG in the postpartum anoestrus dairy cattle. The total of twenty onepostpartum anoestrus dairy cattle used for this study. They were divided into three groupsi.e. (I) treated with single dose injection of 500 ug Gn-RH /im/head (Gn-RH 1x), (II)treated with twice injection of 250 ug Gn-RH/im/head (at 24 hours interval) (Gn-RH 2x),and (III) treated with single dose injection of 1000 IU PMSG/im/head. The result showedthat the concentration of progesterone was no significantly different (P > 0.05) amongPMSG and Gn-RH. However the concentration of progesterone significantly (P < 0.05)increased at 4 days on PMSG and Gn-RH treatmen. In coclusion, PMSG and Gn-RH havethe same respone to elevated of the progesterone.
Keywords: PMSG, Gn-RH, progesterone postpartum anoestrus, dairy cattle